7x-13-4x=7x-6

Simple and best practice solution for 7x-13-4x=7x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-13-4x=7x-6 equation:


Simplifying
7x + -13 + -4x = 7x + -6

Reorder the terms:
-13 + 7x + -4x = 7x + -6

Combine like terms: 7x + -4x = 3x
-13 + 3x = 7x + -6

Reorder the terms:
-13 + 3x = -6 + 7x

Solving
-13 + 3x = -6 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-13 + 3x + -7x = -6 + 7x + -7x

Combine like terms: 3x + -7x = -4x
-13 + -4x = -6 + 7x + -7x

Combine like terms: 7x + -7x = 0
-13 + -4x = -6 + 0
-13 + -4x = -6

Add '13' to each side of the equation.
-13 + 13 + -4x = -6 + 13

Combine like terms: -13 + 13 = 0
0 + -4x = -6 + 13
-4x = -6 + 13

Combine like terms: -6 + 13 = 7
-4x = 7

Divide each side by '-4'.
x = -1.75

Simplifying
x = -1.75

See similar equations:

| x^2-12x+228=0 | | 6x(3x+10)=14 | | 2x+2(x-6)=8x-6(x-10) | | 13xy+14y^2=0 | | 4x+4=-23+x | | lg(3x+4)=2 | | -1+5x=-7x+83 | | -6(1-4a)=66 | | 5x+4=-24+x | | x^6+8x^3-6=0 | | 4x*2+10x+10x+25= | | 0.5h+3=0.7h-3 | | 0.4x-0.2(x+4)=1.4(x+2) | | h=-16t^2+53 | | X^2-15x+5000=0 | | 2x+15=3x+c | | 3+5x+4=17 | | 11(k-1)=7(k-6.333333333) | | 11(k-1)=7(k-6.3333333333) | | 20=44-8(2x-x) | | (x^2-4x+2)(x+(3+i))(x-(3+i))=0 | | 13w-15w=10 | | 11(k-1)=7(k-6.33333333) | | 7m-27=26 | | 1+25y^2+10y=0 | | x^3+3x^2-x+2=3x+5 | | .05(7x+3)=.35(x-1)+.50 | | 6(x+1)+5=2x+4(2+x) | | 5q-12=2q+6 | | .50x+.20y=4.05 | | y=5ln(2x-3) | | -5(x+1)-17=11+2 |

Equations solver categories